AN ANALYSIS OF EFL STUDENTS’ PERCEPTION OF POWERPOINT USED AS ENGLISH LEARNING MEDIA IN CLASSROOM - Rekian Paramasti Ratu; Cahya Komara (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
This study investigated students' perception of PowerPoint software used as learning media in the classroom. The aim of this study to get empirical data or evidence on whether the students' perception of Microsoft PowerPoint they used for studying English, especially EFL students in the classroom. Thus, in this research, the participants involved 900 EFL students in two different layers of the school; junior and senior high schools by applying close-ended and open-ended questionnaires to gather the data. The data was analyzed through quantitative (close-ended questionnaire) and qualitative (open-ended questionnaires) method. The result of the close-ended questionnaire showed that if learning English using Ms. PPT can increase students’ activeness, work up students’ motivation, and improve students’ English competence. In the meantime, the open-ended questionnaire also provided the same findings that more students agreed or said yes (positive side) of learning using MS. PowerPoint. Therefore, it can be concluded that students' perceptions of Ms. PowerPoint were good and exciting. Also, the students felt learning English by using Ms. PowerPoint provided more help, especially in the context of raising activeness, motivation, and English competence in EFL classroom.